Determining the optimal location of the tower crane in building projects using artificial intelligence - مكيه سماح (Latakia University Journal -Engineering Sciences Series, 2022)
Tower cranes are one of the most important equipment used in building projects, their proper placement within the sites boundaries provides a positive impact on the time, operating cost ,productivity and safety of work . Most of the Syrian contracting companies depend on the self-sense and previous experience of the engineers in locating the tower crane, which simply focuses on the possibility of the crane reaching all the supply and demand points, taking into account certain conditions related to the site. This experience does not help placing the crane in the optimal position, Therefore, this research suggests taking advantage of artificial intelligence techniques, especially the Particle Swarm Optimization (PSO) algorithm to place the crane in the optimal location. The new building, Faculty of Dentistry at Tishreen University was chosen as a case study in this research, where the Liebherr 63 LC crane was used on site. The building site boundaries, permanent elements, supply and demand points were modeled within the Revit BIM environment, the crane travel time equations were found as an objective function , and entered to the particle swarm algorithm that was coded in python within Dynamo to reduce objective function’s value in order to find the optimal location of the crane. The results of the proposed algorithm gave accurate 3D coordinates for the optimal position of the crane, reducing the crane travel time by approximately 29% compared to the actual location of the used crane.